2018
DOI: 10.19045/bspab.2018.70002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gibberellic acid and potassium silicate on physiological growth of Okra (Abelmoschus esculentus L.) under salinity stress

Abstract: The aim of this investigation was to improve salt tolerance abilities in okra (Abelmoschus esculentus L.) by foliar application of potassium silicate and seed priming with GA3. A pot experiment was conducted at Awan Nursery Farm, Haripur, to investigate whether seed priming with GA3 and foliar application of potassium silicate could ameliorate the toxic effects of salinity on okra growth. Two okra cultivars Sabz Pari and Mehak Pari were exposed to two levels of NaCl (control and 50mM) according to the saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Salt stress caused a reduction in the growth of all the parameters of the aerial part and the roots of tossa jute plants. This observation is commonly reported for glycophytes such as wheat (Alaoui et al, 2013), tomato (Zhang et al, 2017) rice (Prodjinoto et al, 2018); okra (Ayub et al, 2018;Gouveitcha et al, 2021). In tossa jute, other authors have reported that plant growth was inhibited by salt stress (Ghosh et al, 2013;Ben yakoub et al, 2019).…”
Section: Effect Of Salinity On Plant Growthsupporting
confidence: 60%
“…Salt stress caused a reduction in the growth of all the parameters of the aerial part and the roots of tossa jute plants. This observation is commonly reported for glycophytes such as wheat (Alaoui et al, 2013), tomato (Zhang et al, 2017) rice (Prodjinoto et al, 2018); okra (Ayub et al, 2018;Gouveitcha et al, 2021). In tossa jute, other authors have reported that plant growth was inhibited by salt stress (Ghosh et al, 2013;Ben yakoub et al, 2019).…”
Section: Effect Of Salinity On Plant Growthsupporting
confidence: 60%
“…Generally, applying potassium silicate (K2SiO3) to squash plants increased vegetative growth characters which could be referred to the role of silicon (Si) in extending and encouragement plant roots resulting in enhancing the capability to take up higher nutrients amounts from the soil. Moreover, positive effect of potassium on growth parameters especially dry weights of plant (Ayub et al, 2018 on okra and Abd-Elaziz et al, 2018 on squash).…”
Section: Vegetative Growth Charactersmentioning
confidence: 97%
“…It is rich source of minerals and vitamins; therefore, it is quite popular in both farmers and consumers (Oyelade et al, 2003). Oil of okra is greenish yellow in color that can be used as bio fuel (Anwar et al, 2010;Ayub et al, 2018). A 90% loss (6.5 dSm -1 ) in okra yield has been reported under high salt levels worldwide (Mushtaq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%